The post-Soviet break in economic ties between Russia and Africa: causes and consequences - M. M. Mahamat (Вестник университета, 2024)
The article analyzes the causes and consequences of the post-Soviet breakdown of economic ties between Russia and Africa. The post-Soviet period (since 1991) has led to a breakdown of economic ties between them. It means that trade, investment, and other forms of economic cooperation between the two sides have been significantly reduced or stopped completely. After the collapse of the Soviet Union at the initiative of Mikhail Gorbachev, Africa really became a “non-subject” for diplomats and military personnel stationed in the region, and some economic actors witnessed Moscow’s first initiatives. It was only in early 2018, on the occasion of the arrival of the first shipments of Russian weapons and dozens of “advisers” from Moscow in Bangui, that the French media learned of Russia’s “great comeback” in Africa. This Central African prism powerfully shaped perceptions in Paris: Russian involvement would be a new phenomenon echoing the confrontation between East and West, and Central Africa would be a crucial link in a grand strategy on a continental scale, where Russia would be on its way to establishing itself as a major player. The severing of economic ties between Russia and Africa has negative consequences for both regions, including reduced trade, investment, and political influence, and Russia’s lack of resources and changing political priorities since the collapse of the Soviet Union are the main reasons for it.